“What are we celebrating?”: Nation-Building and The Politics of Independence Commemoration in Ghana - Manuel Jojo MANU-OSAFO; Enoch LAMPTEY; Kofi Takyi ASANTE (E-REA)
National day celebrations are high points in the nation-building project during which citizens and leaders recommit themselves to the “national cause”. But owing to the poignant feelings that these celebrations evoke and the essentially open-ended nature of the nation-building project, rival political factions prefer to use such occasions to assert competing narratives of the nation and to contest authorised visions of the future. These competing narratives, which emerge annually during Ghana’s Independence Day celebrations, became especially charged during the 50th and 60th anniversaries of the country’s independence. We draw on multiple data sources (survey data and public discussions in the national press and on television) to examine the meaning and significance of these debates. We show that even though people agreed that Ghana has not achieved much since independence, they still believed that the country “has a lot to celebrate”. This somewhat paradoxical observation arises from the fact that people distinguished the material from the symbolic aspects of independence in a manner that reflects the prevailing factional, ideological, class and other rifts in society. We argue that because the celebration of the national past is never politically neutral, analysts should never take any particular articulation of the state as self-evident, but should instead ask about its authorship, who stands to benefit or lose from its acceptance, and the strategies adopted to propagate it.